Positive behaviour support in Australian disability policy, and its future with the National Disability Insurance Scheme (NDIS). Issue 1 (2nd January 2019) - Hayward, Brent A.; McKay-Brown, Lisa; Poed, Shiralee
Abstract: Positive behaviour support features prominently in Australian state and federal disability policy, and with the move to the National Disability Insurance Scheme (NDIS), and the continuing role of the states in safeguarding the rights of people with disabilities, the representation of positive behaviour support in Australian policy is an important consideration. Extending a recent review of Australian state positive behaviour support policies, this study examined the NDIS quality and safeguarding framework. Using the concept of policy diffusion, the subject of restrictive practices was used to argue the risks associated with the representation of positive behaviour support in current Australian disability policy. This examination revealed that while positive behaviour support is aligned to the founding principles of the NDIS, it is represented inaccurately in NDIS policy. Further, policies for positive behaviour support are predominantly aligned to restrictive practices and contain inaccurate definitions of positive behaviour support. There is support for imitation and coercion in the diffusion (or "spread") of positive behaviour support policy in Australia, and the potential ramifications for jurisdictions implementing positive behaviour support policy without considering the accuracy of how positive behaviour support is presented is discussed.